Formalizing Public Transit in Mid-Sized Developing Cities: A Review of Strategies for Sustainable and Resilient Mobility - Shahab, Hasan; Mohammed, Hemin (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
Mid-sized cities in developing cities face increasing demand to modernize their public transit (PT) systems to advance sustainability, equity, and resilience. Many of these cities remain dependent on informal transit modes such as minibuses, privately owned taxis, and shared vans which, despite their flexibility, often lead to operational inefficiencies, safety risks, and limited accessibility. This review examines strategies for transitioning to formal public bus transit (BT) systems through analysis of peer-reviewed literature. The analysis is organized around five core domains that directly reflect the structure of this study: assessment of the current state of PT systems, strategies for transitioning from informal to formal networks, selection of appropriate PT modes for mid-sized cities, planning processes for BT systems, and sustainable and resilient approaches for BT development. Based on these findings, this study proposes a structured decision-support framework in the form of a decision tree to guide context-sensitive formalization efforts. Future studies should prioritize long-term impact evaluation, inclusive transition mechanisms for informal operators, and the integration of smart and sustainable technologies.